DINAMIKA KEBIJAKAN FISKAL DAN KINERJA SEKTOR PERTANIAN PADA KABUPATEN/KOTA DI SULAWESI TENGGARA - La Ode Jabuddin; Ayub M. Padangaran; Azhar Bafadal; Budiyanto Budiyanto (Jurnal Sosio Agribisnis, 2019)
This study aims to analyze the dynamics of fiscal policy objectives and the performance of the agricultural sector in the districts/cities in Southeast Sulawesi. The data used in this study is a kind of time series in 2005-2013 in the aggregate, were analyzed descriptively. The results showed that the dynamics of fiscal policy at the district/city in Southeast Sulawesi each year has increased, while the performance of the agricultural sector from the aspect of the GDP and investments also increased, but labor and poor population decreased. By it, in achieving the development goals, the government must increase the number of direct expenditure in the days to come, which is allocated to the provision of public goods, production, and consumption effectively, so that the strategic development targets can be achieved to the fullest.Keywords: dynamics of  fiscal policy; the performance of the agricultural sector; direct expenditure